Flexible Sensor Film Based on Rod-Shaped SWCNT-Polypyrrole Nanocomposite for Acetone Gas Detection - Hyo-Kyung Kang; Jun-Ho Byeon; Hyun-Jun Hwang; Yoon Hee Jang; Jin-Yeol Kim (MDPI Open Access Publishing, 2023)
A nanocomposite rod-shaped structure with a single-walled carbon nanotube (SWCNT) embedded in polypyrrole (PPy) doped with nonafluorobutanesulfonic acid (C4F), SWCNT/C4F-PPy, was synthesized using emulsion polymerization. The hybrid ink was then directly coated on a polyimide film interdigitated with the Cu/Ni/Au electrodes via a screen-printing technique to create a flexible film sensor. The sensor film showed a response of 1.72% at 25 °C/atmospheric pressure when acetone gas of 5 ppm was injected, which corresponds to almost 95% compared to the Si wafer-based array interdigitated with the Au electrode. Additionally, C4F was used as a hydrophobic dopant of PPy to improve the stability of humidity and to produce a highly sensitive film-type gas sensor that provides stable detection even in humid conditions.